2016
DOI: 10.1111/birt.12236
|View full text |Cite
|
Sign up to set email alerts
|

Female Genital Mutilation/Cutting among Women of Somali and Kurdish Origin in Finland

Abstract: The tradition of female genital mutilation/cutting (FGM/C), known to be practiced for example in Africa, Asia and the Middle East, has spread in Europe due to immigration. It has been estimated that half a million girls and women in Europe have been subjected to FGM/C. The procedure has several negative health

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…FGM/C is widely practiced among African‐origin women, and it is associated with several delivery complications in addition to pregnancy complications, such as prolonged labor, obstruction, perineal tears, and postpartum hemorrhage . A previous study found the prevalence of FGM/C was 69% among women of Somali origin and 32% among women of Kurdish origin living in Finland . We are not aware of any previous studies on mode of delivery or delivery complications among migrant Kurdish or Russian women in European countries, making it difficult to compare our results with other studies.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…FGM/C is widely practiced among African‐origin women, and it is associated with several delivery complications in addition to pregnancy complications, such as prolonged labor, obstruction, perineal tears, and postpartum hemorrhage . A previous study found the prevalence of FGM/C was 69% among women of Somali origin and 32% among women of Kurdish origin living in Finland . We are not aware of any previous studies on mode of delivery or delivery complications among migrant Kurdish or Russian women in European countries, making it difficult to compare our results with other studies.…”
Section: Discussionmentioning
confidence: 66%
“…16,17 A previous study found the prevalence of FGM/C was 69% among women of Somali origin and 32% among women of Kurdish origin living in Finland. 18 We are not aware of any previous studies on mode of delivery or delivery complications among migrant Kurdish or Russian women in European countries, making it difficult to compare our results with other studies. Our previous study found that Somali and Kurdish women had higher prepregnancy BMI and Russian women had lower prepregnancy BMI compared with women in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the study by Koukkula et al . in Finland demonstrated the burden of FGM/C among immigrant populations in developed nations with 69% and 32% of women of Somali and Kurdish origins respectively, who had been circumcised (6). Reports have shown that up to 140 million girls and women had undergone FC around the world in 2000; however it is now estimated to be about 200 million in 2016 (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…The acceptance can be facilitated by offering pre-test counselling and correcting any misconceptions regarding the treatment possibilities, normalizing the testing procedure and underlying confidentiality. Another example of a particularly sensitive topic is FGM/C, of which the results of the Maamu Study indicate to be more common among foreign-born women living in Finland than previously assumed (Koukkula et al 2016). Violent traumatic experiences in the former home country were also mostly feasible to ask (Castaneda et al 2017), however, for instance the item of experienced sexual violence was too uncomfortable to be reliably asked especially by some of the male interviewers.…”
Section: Table 1 Overview Of the Interview And Health Examination Mementioning
confidence: 99%